INTEGRASI QAWĀ’ID LUGHAH DAN UṢŪL FIQH DALAM PENAFSIRAN AL-QUR’AN - Musfirah Musfirah; Sohrah Sohrah; Muhammad Galib (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This study of the Qur’an requires methods that can accurately explain the meanings of the text and produce legal understandings that are consistent with the objectives of Islamic law. This research aims to examine the integration of qawāid lughah and uṣūl fiqh in Qur’anic interpretation and to explain their contributions to understanding Qur’anic verses. Employing a library research method, this study draws upon various sources related to Arabic linguistic principles and the foundations of Islamic jurisprudence. The analysis is conducted through linguistic and legal approaches to explore the relationship between these two disciplines in the interpretive process. The findings reveal that qawāid lughah functions to clarify the meanings of words, grammatical structures and the linguistic context of Qur’anic verses, while uṣūl fiqh provides a methodological framework for understanding legal implications and the objectives of Islamic law. These two disciplines are closely interconnected and mutually reinforcing, enabling a more comprehensive understanding of the Qur’an. Therefore, the integration of qawāid lughah and uṣūl fiqh constitutes an essential foundation for developing Qur’anic interpretations that are more accurate, systematic, and academically accountable.